Resection of a nasal arteriovenous malformation with favourable aesthetic outcome: a case report - Hidalgo, Melissa De A.; Ramírez, Axel P.; Chang, Emiliano O.; Vitelly, Antonio U. (International Journal of Research in Medical Sciences, 2024)
This case report details the management of a high-flow arteriovenous malformation (AVM) in a 13-year-old male, a rare condition in pediatric patients. The AVM, located on the left nasal wing, initially presented as a progressively enlarging purple nodule with recurrent bleeding. Initial treatment included embolization on 11 November 2022, which halted growth and led to partial involution. Despite this, renewed bleeding urged further intervention. The patient’s significant medical history, including chronic cardiopathy, added complexity to his care. A two-step treatment approach, including transcatheter embolization followed by surgical resection, achieved approximately 95% devascularization. The post-operative course showed satisfactory recovery with no complications. This case highlights the effectiveness of a multidisciplinary approach in managing complex facial AVMs and underscores the need for ongoing monitoring and individualized treatment strategies.